Molecular cloning and mRNA expression of IFIT5 in tissues of ducklings infected with virulent duck hepatitis A virus type 3. (June 2019) - Zhang, Xuelian; Zhang, Wenjing; Liu, Yue; Qi, Haihui; Hao, Chunxue; Zhang, Wenlong; Gao, Mingchun; Wang, Junwei; Ma, Bo
Abstract: Interferon-induced proteins with tetratricopeptide repeats (IFITs) are a family of proteins strongly induced downstream of type I interferon signaling. The function of IFITs has been investigated extensively in mammals. IFIT5 is the sole protein in this family found in birds and little information is available about the function of avian IFIT5. In this study, duck IFIT5 was cloned from peripheral blood mononuclear cells. Multiple amino acid sequence alignment and phylogenetic analysis showed that duck IFIT5 is highly homologous to chicken IFIT5 . Tissue specificity analysis demonstrated that duck IFIT5 was ubiquitously expressed in all examined tissues of five-day-old ducklings, with the highest expression levels in heart, followed by thymus, cerebrum, liver, and lung; kidney expressed the lowest. Quantitative real-time PCR (qRT-PCR) analysis revealed that duck IFIT5 expression rapidly increased both in vitro and in vivo after stimulation with polyinosinic:polycytidylic acid [poly (I:C)] and infection with virulent duck hepatitis A virus type 3 (DHAV-3), respectively. Altogether, these results indicate that the expression of duck IFIT5 is positively correlated with viral load and may play an important role in the immune response to DHAV-3 infection. This study lays a foundation for further research into the innate antiviral immune responses of ducklings. Highlights: Duck IFIT5 gene was amplified, and the phylogenetic analyses and protein structural features were described. Duck IFIT5 was ubiquitously expressed in five-day-old duck different tissues. Duck IFIT5 expression induced by poly (I:C) stimulation in a concentration- and time-dependent manner. Expression profiles of duck IFIT5 in the liver and spleen of ducklings after DHAV-3 infection were detected. Duck IFIT5 expression in euthanized ducklings following DHAV-3 infection was detected.